(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Background: The majority of working women chose public transportation, as evidenced by the daily lives of people from all walks of life in cities. Unfortunately, they are vulnerable to verbal, physical, psychological, and financial harassment from their fellow passengers and bus operators during their route. Cases of this nature are rarely reported in the mainstream arenas. As a result, the current study is significant. Materials and Methods: In this regard, an assessment through a questionnaire based cross-sectional study of the prevalence and factors associated with sexual harassment while utilizing public transit in the Sonitpur district of Assam has been made. A stratified random sample of 600 young women who used public transportation was recruited. Results: 79.83% of all young women study participants have been harassed in the last six months. Unmarried women (76%) travelling by bus (76.67%) in the evenings (79.67%) were more vulnerable to being harassed by middle-aged (55%) fellow passengers (92%). Such incidents were higher in festive seasons (69%). Unfortunately, the cases were not reported. Conclusion: Sexual harassment on the transit is a major setback for working women and indirectly affects the country’s growth and development. This menace needs to be addressed aggressively.